Erratum: Indonesian Peer to Peer Lending (P2P) at entrant’s disruptive trajectory - Kohardinata, Cliff; Soewarno, Noorlailie; Tjahjadi, Bambang (Business: Theory and Practice, 2021)
The article “Indonesian Peer to Peer Lending (P2P) at entrant’s disruptive trajectory” by Cliff Kohardinata, Noorlailie Soewarno, Bambang Tjahjadi, published on 17 February 2020 in the research journal Business: Theory and Practice, 21(1), 104−114, https://doi.org/10.3846/btp.2020.11171, contained a following error on 104 p.:The affiliations were mixed. They should read:Cliff KOHARDINATA1, Noorlailie SOEWARNO2, Bambang TJAHJADI31, 2, 3Faculty of Economics and Business, Universitas Airlangga, Surabaya, Indonesia 1Faculty of Management and Business, Universitas Ciputra, Surabaya, Indonesia Corrected version of the article is available online.The publisher apologises for this error.